Mesenchymal Stem Cell Exosomes as a New Strategy for the Treatment of Diabetes Complications - Xiong, Jiachao; Hu, Hao; Guo, Rong; Wang, Hui; Jiang, Hua (Frontiers in Endocrinology, 2021)
Diabetes mellitus (DM) is a metabolic disease, now prevalent worldwide, which is characterized by a relative or absolute lack of insulin secretion leading to chronically increased blood glucose levels. Diabetic patients are often accompanied by multiple macrovascular complications, such as coronary heart disease, hypertension, macrovascular arteriosclerosis, and microvascular complications. Microvascular complications include diabetic kidney injury, diabetic encephalopathy, and diabetic foot, which reduce the quality of life and survival status of patients. Mesenchymal stem cell exosomes (MSC-Exos) possess repair functions similar to MSCs, low immunogenicity, and ease of storage and transport. MSC-Exos have been proven to possess excellent repair effects in repairing various organ damages. This study reviews the application of MSC-Exos in the treatment of DM and its common complications. MSC-Exos may be used as an effective treatment for DM and its complications.